An empirical study on the effect of a driving companion bot on anger coping behaviors - Yoo, Youngjae; Lee, Jiin; Kim, Naeun; Yang, Min-young; Lee, Seunghoon; Kim, Jinwoo (Behaviour & information technology, 2023)
When anger is abruptly triggered during driving, it becomes difficult to control one's feelings. In this situation, other people can help mediate the angry emotional state through social interaction. However, it is not feasible to expect a passenger's help for controlling the driver's anger during every single drive. Failure to control the driver's anger can lead to road rage, which can cause a critical danger. In this study, we addressed these concerns by designing and evaluating a driving companion bot that helps drivers control their anger. The bot was designed to deliver verbal comments which was developed based on five different cognitive coping strategies to the driver when the driver faced anger-inducing situations while driving. A within-subjects lab experiment was conducted with 38 participants who had driver's licences. The results indicated that the use of a blaming others coping strategy was the most effective for anger reduction, perceived empathy, and companionship with no additional cognitive load compared to other strategies. Feedback from a post-experiment interview was also presented to discuss the long-term application of the study results. This includes theoretical findings and practical implications for designers and stakeholders focused on safe driving.